Genèse des formations en urbanisme en France : Grenoble un “laboratoire urbain” pas comme les autres ? - Jennifer Buyck; Samuel Martin; Maryvonne Prévot; Fleur Romano (Territoire en Mouvement)
At the time of many Grenoble fiftieth anniversary celebrations - that of the AURG Urban Planning Agency of Grenoble Region in 2017, that of the Winter Olympics in 2018, that of the Villeneuve -, we propose a history of the Institut d’Urbanisme de Grenoble based on an original exploration of its archives as well as on interviews of former teachers and students. Founded in 1969 under the name Unité d’Enseignement et de Recherche - Urbanisation, Aménagement, the Urban Planning Institute of Grenoble (attached to the University of Social Sciences and later to the University Grenoble-Alpes) emerged from the effervescence of May 1968 but also from the election a few years earlier (1965) of a team inspired by a renewed municipal socialism (Municipal Action Group led by Hubert Dubedout). In order to emancipate itself from state supervision, the "Grenoble urban laboratory" then acquired both an Urban Planning Agency and a training and experimentation tool in the field of teaching and research in urbanism, urbanization and planning. Why are we talking about experimentation? Because the initial pedagogical project is not common. Contrary to other trainings in urban planning from the same period, in Grenoble, in an Institute “ouvert à quatre vents”, they focused on a dual training: on one hand a doctoral program, that led to a PhD and on the other hand continuing education. Research seminars, internships and case studies (before being called field workshops then project workshops) formed the students’ schedules. By analyzing the links to the professional, political and activist worlds, by understanding the relations with other academic disciplines (architecture, law, economics, engineering, geography, psychology and sociology) and with urban research and contractual structures Finally, by studying, finally, the processes of institutionalization and territorial anchoring, we demonstrate how and when Grenoble’s pedagogy of urban planning has proved innovative. The foundations and scope of this training will be discussed. Besides, this history of the Grenoble Institute of Urbanism is also a way of questioning the evolution of the urban discipline (doctrines and practices), notably through the trajectories of influential personalities, academics or practitioners who punctuated the life of the Institute (Jean Verlhac, Claude Domenach, Jean-François Parent, Christian Lacroix, ...). Its evolution is also revealing of the ideas and contexts that found it and run through it (ZUP and major ensembles revisited, revitalization of old centers, creation of social and cultural facilities, citizen participation to the contemporary problems of metropolis). It can be observed by the workshop themes and issues addressed in theses, study reports and student trajectories, whether in or outside France